PENGARUH PROMOSI KESEHATAN TANDA BAHAYA KEHAMILAN TRIMESTER III TERHADAP PENGETAHUAN IBU HAMIL - Nanda Hotman; Izzawati Arlis; Fitriyani Bahriyah (Journal of Midwifery and Health Administration Research, 2022)
Background: The danger sign of pregnancy is a sign that a serious problem has occurred in the pregnant woman or the fetus she is carrying. Health promotion of pregnancy danger signs identifies knowledge of pregnant women after being given health promotion and analyzes the effect of health promotion on pregnancy danger signs on knowledge of pregnant women. This study aimed to determine the effect of health promotion on the third trimester of pregnancy danger signs on the knowledge of pregnant women in RSUD Indrasari Rengat. Methods: The research method used is descriptive analytic with a Group Pretest-Postest research design. The sampling technique used was consecutive sampling with a total of 38 pregnant women. The results were analyzed using paired sample t-Test. Results: The average value of knowledge of pregnant women before being given health promotion was 72.18 and after being given health promotion was 85.39 with t -11.086 and the significance was less than 5% (p=0.000<0.05). Based on the results of these studies, it can be concluded that there are differences in the knowledge of respondents before and after being given a promotion. Conclusion: Health promotion about the danger signs of pregnancy influences pregnant women’s knowledge in the III trimester